Controversies in uro-oncology - Wiegel, Thomas; Heicappell, R.; Miller, Kurt; Hinkelbein, Wolfgang 1948- (Frontiers of radiation therapy and oncology, 2002)
Over the past few years, tremendous progress has been made in the development of therapies for prostate and bladder cancer. As a consequence, greatly improved surgical techniques as well as new forms of radiotherapy, chemotherapy and hormonal therapy are now available. This interdisciplinary approach is reflected in the broad scope of this volume, which aims to provide an overview of current treatment strategies for bladder and prostate cancer. The first part of the book discusses the optimization of radiation techniques like 3 D planning or IMRT and focuses on definitive radiotherapy with or without adjuvant or neoadjuvant hormonal manipulation. The quality of life after therapy is another important issue. Further chapters deal with radical cystectomy and organ preservation by radio-chemotherapy as well as the treatment of T1G3 cancer. In the last part, the emphasis lies on brachytherapy, which has become increasingly important for the treatment of prostate cancer.This book will be of great value to urologists and radiation oncologists as well as to all others involved in the care of patients with urologic cancer